Taxation of a Venture Capitalist with a Portfolio of Firms - Christian Keuschnigg (Center for Economic Studies and ifo Institute (CESifo), 2002)
Venture capitalists not only finance but also advise and thereby add value to young innovative firms. The prospects of venture capital backed firms thus depend on joint efforts of entrepreneurs and informed venture capitalists, and are subject to double moral hazard. In financing a portfolio of firms, venture capitalists additionally face a trade-off between the number of companies and the amount of managerial advice allocated to each individual venture. The paper argues that managerial support and the number of portfolio firms are inefficiently low in private equilibrium. An optimal tax policy is derived that succeeds to move the private equilibrium towards a first best allocation.
Keywords: 330; venture capital; double moral hazard; optimal taxation